2010
DOI: 10.4146/jjspopsy.2010-066
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search Behavior of Experienced Players while Anticipating the Success of Basketball Free Throws

Abstract: The purpose of this study was to compare the visual search behaviors of experienced basketball players with those of novices as they anticipated the success of a free throw. In basketball, the accurate judgment of the result of a free throw at an early time is an important factor in both performing the next play for the players and in deciding team tactics for coaches. The subjects were twelve experienced male basketball players and twelve novice counterparts. The task was to anticipate the success of free thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The present study of visual search acitivity at a normal speed showed a tendency consistent with the results which were obtained by Ishibashi et al (2010). The novice group focused their gaze (fixation rate of more than 80%) initially on the upper body region and subsequently on the ball's trajectory at normal video speeds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study of visual search acitivity at a normal speed showed a tendency consistent with the results which were obtained by Ishibashi et al (2010). The novice group focused their gaze (fixation rate of more than 80%) initially on the upper body region and subsequently on the ball's trajectory at normal video speeds.…”
Section: Discussionsupporting
confidence: 93%
“…It had been speculated that basketball players could predict shot outcomes by capturing variables in the shooter's knee, wrist and finger joint angles (Aglioti et al, 2008). Following that, it was revealed that the experienced basketball players' viewing points were distributed on the shooter's lower body and arms (Ishibashi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average time and number of fixations in the AOI of the expert athlete were significantly greater than those of the novice, which showed that the expert spent more time on the essential information and examined that region more frequently. Studies have shown that experienced basketball players can predict whether the ball will go through the hoop by observing the angle variables of the shooter's lower body and arm, wrist, and finger joints (Yukimasa et al., 2010 ). In this study, through the heat map of eye‐movement for two groups, it was found that the focus area of the expert was the player's body and arm.…”
Section: Discussionmentioning
confidence: 99%